Comparison of Different Risk-Stratification Systems for the Diagnosis of Benign and Malignant Thyroid Nodules - Shen, Yan; Liu, Miao; He, Jie; Wu, Shu; Chen, Ming; Wan, Yonglin; Gao, Linjun; Cai, Xiaoyan; Ding, Jun; Fu, Xiaohong (Frontiers in Oncology, 2019)
Introduction: To compare the efficacy of four different ultrasound-based risk-stratification systems in assessing the malignancy risk of thyroid nodules in the Chinese population. Methods: We retrospectively reviewed the digital ultrasound images of 1,568 patients (1,612 thyroid nodules) who underwent surgery in our hospital between January 2012 and December 2017. All thyroid nodules were pathologically identified as malignant or benign. We evaluated the following ultrasound characteristics: size, location, composition, echogenicity, shape, margins, calcification or echogenic foci, and extrathyroidal extension. Each nodule was categorized using four risk-stratification systems: the American Thyroid Association (ATA) classification, the Thyroid Imaging, Reporting, and Data System (TIRADS) of the American College of Radiology (ACR-TIRADS), the European Thyroid Association TIRADS (EU-TIRADS), and the TIRADS developed by Kwak et al. (Kwak-TIRADS). The diagnostic performance of each risk-stratification system relative to the pathological results was analyzed. We used receiver operating characteristic curves to identify cutoff values that yielded optimal sensitivity (SEN), specificity (SPE), positive predictive value (PPV), negative predictive value (NPV), and accuracy (ACC). Results: Of the 1,612 nodules, 839 (52.0%) were benign, and 773 (48.0%) were malignant. The AUCs of the ACR-TIRADS, EU-TIRADS, Kwak-TIRADS, and ATA classification were 0.879, 0.872, 0.896, and 0.869, respectively. The Kwak-TIRADS had the best SEN, NPV, ACC, and AUC, while the ACR-TIRADS had the best SPE and PPV. Conclusion: All four risk-stratification systems had good diagnostic performances (AUCs > 86%). Considering its high SEN, NPV, ACC, and AUC, we believe that the Kwak-TIRADS may be the more effective risk-stratification system in the Chinese population.